2019
DOI: 10.1007/s13197-019-04138-1
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics: an emerging threat to food security and human health

Abstract: Microplastic presence in seafood and foodstuff have been documented globally in recent studies. Consequently, human exposure to microplastics through the ingestion of contaminated food is inevitable and pose a risk to food security and human health. In this review, microplastics and related xenobiotics are defined, global evidence of microplastic pollution in seafood is reviewed, the impacts to commercial marine species and food security are discussed, and the current knowledge of its direct effects on human h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
123
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(132 citation statements)
references
References 79 publications
1
123
0
8
Order By: Relevance
“… 6 Moreover, MPs and NPs could transfer through the food chain and eventually enter organisms through the skin, respiratory tract, and digestive tract. 2 , 7 , 8 It has been reported that plastic particles (≤0.3 μm) could reach and accumulate in the liver, spleen, and lymphatic systems of rodents. 9 A surveying on eight healthy volunteers from Europe and Asia showed that up to nine types of MPs including polypropylene and polyethylene terephthalate have been detected in human stool samples.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Moreover, MPs and NPs could transfer through the food chain and eventually enter organisms through the skin, respiratory tract, and digestive tract. 2 , 7 , 8 It has been reported that plastic particles (≤0.3 μm) could reach and accumulate in the liver, spleen, and lymphatic systems of rodents. 9 A surveying on eight healthy volunteers from Europe and Asia showed that up to nine types of MPs including polypropylene and polyethylene terephthalate have been detected in human stool samples.…”
Section: Introductionmentioning
confidence: 99%
“…Plastics reach the marine environment through land-or sea-based sources (Andrady, 2011), and have become a persistent and ubiquitous pollutant in the ocean (Hitchcock and Mitrovic, 2019). Microplastics are plastic particles smaller than 5 mm in diameter (Andrady, 2017;Crawford and Quinn, 2017), and can be classified in two categories: primary and secondary microplastics. Manufactured plastic particles of microscopic size are considered primary microplastics (Cole et al, 2011), while secondary microplastics are fragmented particles derived from larger plastics (Shim et al, 2018) due to its exposure to mechanical fragmentation and photolytic and biological degradation (Browne et al, 2007).…”
mentioning
confidence: 99%
“…Microplastics are ubiquitous in the environment, being found in marine sediments (De-la-Torre et al, 2020;Hidalgo-Ruz and Thiel, 2013), marine and continental waters (Mao et al, 2020;Sun et al, 2018), terrestrial and agricultural environments (Dioses-Salinas et al, 2020;Piehl et al, 2018). The widespread distribution and small size of microplastics make them readily bioavailable to marine biota (De-la-Torre, 2020). Thus, ingestion of microplastics has been reported in organisms across different trophic levels (e.g., zooplankton, mollusks, and fish), up to apex predators, such as marine mammals and seabirds (Bessa et al, 2019;Desforges et al, 2015;Garcés-Ordóñez et al, 2020;Gedik and Eryaşar, 2020;Ory et al, 2017;Santillán et al, 2020).…”
Section: Introductionmentioning
confidence: 99%